Research on the Development Status and Countermeasures of China’s Integrated Energy Service Stations - Ye, Lin (International Journal of Electric Power and Energy Studies, 2025)
Against the backdrop of the global energy revolution and China’s “dual carbon” goals, integrated energy service stations-new infrastructure combining multi-energy supply (oil, gas, electricity, hydrogen, storage) and smart services-have become key enablers of clean transportation energy transition and the new energy system. This paper systematically reviews the development landscape of China’s integrated energy service stations. It finds that, driven by top-level policies and market exploration, the sector has entered a fast lane of large-scale and diversified growth, with co-located stations as the mainstream model and growing trends toward smart and eco-friendly operations. However, development is still constrained by weak planning and approval coordination, lagging technical integration and standards, severe early-stage economic challenges, and complex cross-energy safety management. Drawing on domestic and international best practices, this paper proposes systematic countermeasures: strengthening top-level design and “multi-plan integration,” building an innovation system that pairs technology breakthroughs with standard leadership, creating “energy-plus” value-ecosystem business models, and erecting a full-chain smart safety defense, aiming to provide decision-making references for high-quality and sustainable development of China’s integrated energy service stations.